2018
DOI: 10.1002/ccd.28029
|View full text |Cite
|
Sign up to set email alerts
|

Mid‐term outcomes (up to 5 years) of percutaneous edge‐to‐edge mitral repair in the real‐world according to regurgitation mechanism: A single‐center experience

Abstract: Objectives To report mid‐term results after MitraClip repair, according to mitral regurgitation (MR) mechanism, in a real‐world single‐center experience. Background Mid‐term outcomes of percutaneous edge‐to‐edge mitral repair in the real world are still limited. Methods We assessed the follow‐up results of patients treated with MitraClip at a single high‐volume mitral center from 2008 to 2016. All patients underwent Heart‐Team discussion, prospective data collection and enrolment in a dedicated outpatient clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 31 publications
(49 reference statements)
4
17
0
Order By: Relevance
“…Higher all-cause mortality at follow-up in sMR patients was found, and might be explained by the advanced age of sMR patients, a more impaired baseline LV and RV function compared to pMR patients. Similar findings were presented in the Buzzatti et al [22] showed higher 5-year mortality (about 50%) with good mid-term results including reduction of MR and improved symptoms in 339 patients with relevant MR. In line with current results, they found pronouncedly worse outcomes and higher mortality in patients with secondary MR associated with worse LV remodelling and function.…”
Section: Survival and Re-intervention Ratessupporting
confidence: 88%
See 1 more Smart Citation
“…Higher all-cause mortality at follow-up in sMR patients was found, and might be explained by the advanced age of sMR patients, a more impaired baseline LV and RV function compared to pMR patients. Similar findings were presented in the Buzzatti et al [22] showed higher 5-year mortality (about 50%) with good mid-term results including reduction of MR and improved symptoms in 339 patients with relevant MR. In line with current results, they found pronouncedly worse outcomes and higher mortality in patients with secondary MR associated with worse LV remodelling and function.…”
Section: Survival and Re-intervention Ratessupporting
confidence: 88%
“…Moreover, Matsumoto et al [10] found that pre-existing pulmonary hypertension was a strong predictor of higher all-cause mortality 12 months after the MitraClip procedure. The association between worse outcomes and advanced heart disease and symptoms have been presented by Buzzatti et al [22] in more than 300 patients with relevant MR at 5-year follow-up. The cited study validates present findings; elevated baseline sPAP values are an independent predictor of (> 45 mmHg) adverse outcomes and (> 50 mmHg) all-cause mortality at 5-year follow-up.…”
Section: Predictors Of Adverse Outcomementioning
confidence: 89%
“…7 Comparable to the surgical setting, higher rMR grades after MitraClip therapy are also associated with a recurrence of severe MR grades and higher rates of rehospitalization due to heart failure. [8][9][10][11][12] Based on these findings and the largest single centre MitraClip experience so far, the aim of this retrospective observational study was to assess the impact of very low and low rMR (≤1+) grades at discharge on long-term outcome and durability in comparison to moderate (2+) and more severe rMR (≥3+) grades in patients with FMR.…”
Section: Introductionmentioning
confidence: 99%
“…Previous trials and registries have assessed the prognostic impact of NYHA functional class 26,27 . A recently conducted multicentre study involving more than 800 patients from the German Mitral Valve Registry showed a lower survival rate at short-term follow-up in patients with baseline NYHA class IV in comparison to those on other functional classes 26 .…”
Section: Discussionmentioning
confidence: 99%